Correlação entre textura superficial e corrosão de conjugados processados por PAPVD: monocamada e duplex Cr-N - Janaina Kizzi de Morais Silva (2004)
Thin films processed by PAPVD are used with coatings of steel to improve the steel performance in wear, fatigue and corrosion. The performance of coatings processed by PAPVD depends of couple (substrate and coating) characteristics because of electrochemical action in the metallic corrosion. Examples of characteristics are the coating adhesion, the presence of porosity and pinholes in the coating and the chemical reactivity of substrate after the coating deposition. The duplex coatings, consisting of nitriding of steel and subsequent deposition of coating, has high performance in abrasive wear applications. The nitriding of steel (duplex treatment) changes the superficial texture (roughness) of the system, it influences the chemical reactivity and the corrosion resistance. This work have evaluated the corrosion resistance of four systems: tempered H13 steel; tempered and nitrided H13 steel; Cr-N single-layered coupled (steel coated with a thin film processed by PAPVD) and Cr-N duplex coupled (steel nitrided and coated with a thin film processed by PAPVD). The influence of nitriding of steel in the corrosion resistance had been studied and a correlation between superficial texture and corrosion was made. For this correlation, it wasutilized parameters of superficial roughness provided through of the profilometry technique and parameters of corrosion provided through of the corrosion techniques